Karakteristik Ibu yang Tidak Memberikan Asi Eksklusif di Puskesmas Bajeng Kabupaten Gowa - Karnelyi Karnelyi; Sitti Saleha; Rahmatiah Rahmatiah (Universitas Muhamadiyah Manado, 2024)
Exclusive breastfeeding for newborns is an effort to prevent infectious diseases, malnutrition and death in babies and toddlers. The achievement of exclusive breastfeeding is still low, indicating that there are factors preventing mothers from giving exclusive breastfeeding for six months to their babies. The low number of breastfeeding mothers is motivated by the lack of awareness among mothers regarding the importance of breast milk for the growth and development of their children. This study aims to determine the characteristics of mothers who do not provide exclusive breastfeeding at the Bajeng Community Health Center, Gowa Regency. The method used in this research is a descriptive design which is a type of analytical and observational research design with a total sample of 30 people selected using total sampling techniques. The results of the research showed that of the 30 respondents, 24 respondents were able to provide exclusive breastfeeding with the age of 20-35 years and the highest number of domestic workers were 18 respondents or (100%), while in terms of family support the highest number of respondents were able to provide exclusive breastfeeding were 12 respondents or (66.7%). In terms of education, the highest number of mothers who were able to provide exclusive breastfeeding were high school/vocational school education with 17 respondents or (56.7%) and the highest number of mothers who were able to provide exclusive breastfeeding were primigravida mothers with 8 respondents.